Crack Analysis of Reinforced High Strength Concrete Elements in Simulated Aggressive Environments. (2016) - Negrutiu, Camelia; Sosa, Ioan Pavel; Constantinescu, Horia; Heghes, Bogdan
Abstract: In nowadays social and economic demands of rapid construction and durable behavior of building systems, high strength concrete is the material choice, with both rapid strength development and improved performance to aggressive environments. However, the performance of reinforced high concrete elements differs from that of ordinary concrete elements and the lack of design standards delays the implementation of the high strength concrete in private practice. Moreover, the service life performance, more specific, the durability of high strength concrete elements still remains difficult to assess, especially because of the inherent structural cracks that conduct the aggressive media to the embedded reinforcement, thus causing corrosion and possible failure of the element. The objective of the present study is to investigate the influence of the cracking pattern of reinforced high strength concrete elements exposed to accelerated corrosion on the structural behavior of the elements, with concrete cover of 25 and 50 mm. Witness specimens are used for comparison. The results of the study show that the influence of the reinforcement corrosion is more important on the 25 mm concrete covers, with the development of larger crack widths in lower stages of loading than for elements with 50 mm covers. However, the overall performance of the high strength concrete elements exposed to accelerated corrosion was above the theoretical, standard based, design capacity of structural members.